Padlet-Based Collaborative Writing and Digital Competence in EFL Academic Writing: Evidence from Indonesian Higher Education - Siti Musarokah; Issy Yuliasri; Sri Wuli Fitriati; Widhiyanto Widhiyanto; Ngasbun Egar (Jurnal Ilmiah Peuradeun, 2026)
This study addresses a limitation in digital collaborative writing research by positioning digital competence as a moderating mechanism shaping students’ participation in Padlet-based collaborative academic writing, rather than treating it as a background learner characteristic. Previous studies have mainly examined learning outcomes or engagement when using collaborative platforms, with limited attention to how differences in digital competence influence collaborative interaction processes in technology-mediated writing environments. Using an explanatory sequential mixed-methods design, this study involved 30 undergraduate students in an Academic Writing course at a private Indonesian university. Data were collected through a digital competence questionnaire, pre- and post-writing tests, and semi-structured interviews. The findings show that Padlet supported improvements in idea organization, peer interaction, and higher-order writing performance, while digital competence shaped students’ interaction strategies and participation patterns. This study contributes by demonstrating that digital competence is a key mechanism influencing collaborative writing participation in higher education digital learning environments.